Androgen receptor expression in recurrent granulosa cell tumor of the ovary: Clinical considerations of treatment and surveillance in a transgender male - Jordyn Tumas; Ruben D. Alberto Hiraldo; Tara Berman (Gynecologic Oncology Reports)
Granulosa cell tumors (GCT) represent a rare subtype of ovarian cancers. A majority of these tumors express androgen receptor (AR), making them hormonally sensitive. AR positivity not only suggests a potential role of anti-androgen therapy in treating these tumors but also poses a cause for concern: female to male (FTM) transgender patients undergoing exogenous testosterone therapy may be at risk for recurrence, progression, or even incidence of this type of cancer. Although treatment of GCT in transgender individuals has not been well-described, the impact of exogenous hormone use on cancer physiology and treatment should be considered, while also addressing gender dysphoria throughout treatment and in surveillance. Here, we describe a FTM transgender patient with recurrent AR-positive adult granulosa cell tumor after starting testosterone supplementation, along with a literature review to explore the current knowledge of ovarian changes observed following FTM gender transition and subsequent risk of ovarian cancer.